Effectiveness of Phenylephrine in the Treatment of Subarachnoid Block Induced Hypotension During Elective Caesarean Section - A Comparative Study with Ephedrine (East West Medical College Journal, 2026)
Background: Maternal hypotension is one of the common complications after spinal anesthesia for cesarean delivery, resulting in adverse maternal and fetal outcomes. The selection of the most efficient treatment is one of the main challenges in obstetric cases. Prompt treatment of hypotension with intravenous vasopressor is necessary to avoid these maternal and fetal effects. This study will set to compare phenylephrine’s effectiveness in treating subarachnoid block induced hypotension in relation to ephedrine during elective lower uterine cesarean section (LUCS) under the subarachnoid block (SAB). Objectives: The study objective is to compare the effects of a bolus dose of ephedrine versus phenylephrine in treating subarachnoid block-induced hypotension during elective lower uterine cesarean section. Study of Place: Department of Anesthesiology & Intensive Care Unit (ICU), East West Medical College, Dhaka, Bangladesh. Study period: From September 2023 to February 2024. Study design: Prospective, randomized, double-blinded trial Method: The study population was women undergoing lower uterine cesarean section (LUCS) who fulfilled the selection criteria. The study sample was selected by prospective, randomized, double-blinded trial. Ninety patients were enrolled in this study and allocated equally into Group A (Ephedrine administered group) and Group B (Phenylephrine administered group). All relevant data were collected and analyzed with a statistical package of social science (SPSS) version 23 software, and all the statistical tests were considered significant when p value